Two-dimensional spin-gapless semiconductors: A mini-review - Wang, Jianhua; Wang, Dandan (Frontiers in Chemistry, 2022)
In the past decade, two-dimensional (2D) materials and spintronic materials have been rapidly developing in recent years. 2D spin-gapless semiconductors are a novel class of ferromagnetic 2D spintronic materials with possible high Curie temperature, 100 % spin-polarization, possible one-dimensional or zero-dimensional topological signatures, and other exciting spin transport properties. In this mini-review, we summarize a series of ideal 2D SGSs in the last three years, including 2D oxalate-based metal-organic frameworks, 2D single-layer Fe2I2, 2D Cr2X3 monolayer with the honeycomb kagome (HK) lattice, 2D CrGa2Se4 monolayer, 2D HK Mn–cyanogen lattice, 2D MnNF monolayer, and 2D Fe4N2 pentagon crystal. The mini-review also discusses the unique magnetic, electronic, topological, and spin-transport properties and the possible application of these 2D SGSs. The mini-review can be regarded as an improved understanding of the current state of 2D SGSs in recent three years.